2021
DOI: 10.1038/s41598-021-94988-7
|View full text |Cite
|
Sign up to set email alerts
|

Recent trends in revision knee arthroplasty in Germany

Abstract: We aimed to answer the following questions: (1) How did numbers of revision knee arthroplasty procedures develop in Germany over the last decade compared to primary TKA? (2) How high was the percentage of septic interventions in knee prosthesis revisions? (3) Which treatment strategy was chosen for surgical treatment of knee PJI? Revision arthroplasty rates as a function of age, gender, infection and type of prosthesis were quantified based on Operation and Procedure Classification System codes using revision … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 24 publications
0
9
1
Order By: Relevance
“…TKAs, like any surgery, are susceptible to complications and reoperations. A study by Rupp et al of all TKAs performed in Germany in 2018 concluded that 12.6% of them required revision surgery, 16 which is slightly higher than in our cohort. The main causes of revision TKA described in literature are aseptic loosening (20.3-23.1%), infection (18.4-20.4%), bearing surface wear (3.2-18.1%), instability (17.7%), and pain or stiffness (9.3%).…”
Section: Discussioncontrasting
confidence: 68%
“…TKAs, like any surgery, are susceptible to complications and reoperations. A study by Rupp et al of all TKAs performed in Germany in 2018 concluded that 12.6% of them required revision surgery, 16 which is slightly higher than in our cohort. The main causes of revision TKA described in literature are aseptic loosening (20.3-23.1%), infection (18.4-20.4%), bearing surface wear (3.2-18.1%), instability (17.7%), and pain or stiffness (9.3%).…”
Section: Discussioncontrasting
confidence: 68%
“…Interestingly, our analysis revealed substantially lower revision rates due to PJI after UKA compared to revision due to PJI after TKA, which has been reported to be around 20–30% [ 12 15 ]. Reason for lower PJI revision rates in UKA might be the key drivers for aseptic revision surgery after UKA which have been described as osteoarthritis of another compartment and aseptic loosening after UKA [ 10 ].…”
Section: Discussionmentioning
confidence: 64%
“…Despite continuous improvements in the pre-, peri- and postoperative treatment of fractures and joint replacements, we are experiencing a steadily increasing rate of infections after surgery [ 3 , 7 ]. The demographic change, the annually growing proportion of patients with metabolic syndrome, further comorbidities and sequelae are potential explanations for this phenomenon.…”
Section: Discussionmentioning
confidence: 99%
“…An increasing rate of almost 25% for total knee arthroplasties performed in Germany was reported in the last decade. Likewise, septic revisions due to PJI increased by over 50% within the last decade [ 6 , 7 ]. Similarly, an incidence of PJI between 23.5 and 27.8 per 100,000 inhabitants in Germany was detected and showed constant growth [ 8 ].…”
Section: Introductionmentioning
confidence: 99%